Information Technology, Organizational Restructuring and the Future of Middle Management - Dopson, S (1993)
This article examines the impact of information technology as one of the factors affecting the numbers and roles of middle managers. The authors highlight the need to empirically examine middle management work in the context of the complexity of changes affecting the job of middle managers and the complexity of reactions to these changes, if further assertions about the future of middle management are to be avoided.